2020
DOI: 10.1016/j.molp.2020.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Mimics for Elucidating Zaxinone Biology and Promoting Agricultural Applications

Abstract: Zaxinone is an apocarotenoid regulatory metabolite required for normal rice growth and development. In addition, zaxinone has a large application potential in agriculture, due to its growth-promoting activity and capability to alleviate infestation by the root parasitic plant Striga through decreasing strigolactone (SL) production. However, zaxinone is poorly accessible to the scientific community because of its laborious organic synthesis that impedes its further investigation and utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 44 publications
(51 reference statements)
7
38
0
Order By: Relevance
“…Baz et al, 2018;Yoneyama et al, 2020 Abscisic acids NCEDs A phytohormone involved in plant abiotic and biotic stress response as well as in many developmental processes including seed dormancy. of zaxinone as well as of zaxinone mimics increased the growth of crown roots of rice seedlings and alleviated Striga-infestation in a Striga-susceptible rice cultivar, by reducing SL content and release (Wang et al, 2019a(Wang et al, , 2020a, demonstrating its application potential for improving rice growth and combating root parasitic weeds. Very recently, Wang et al (2021) also demonstrated that increased sugar uptake and metabolism is likely the major reason for growth-promoting activities of zaxinone in rice and that zaxinone effect on root cell division activity in root meristem and on the number of cortex cell layers is likely caused by modulating cytokinin content.…”
Section: The Significance and Function Of Apocarotenoidsmentioning
confidence: 97%
“…Baz et al, 2018;Yoneyama et al, 2020 Abscisic acids NCEDs A phytohormone involved in plant abiotic and biotic stress response as well as in many developmental processes including seed dormancy. of zaxinone as well as of zaxinone mimics increased the growth of crown roots of rice seedlings and alleviated Striga-infestation in a Striga-susceptible rice cultivar, by reducing SL content and release (Wang et al, 2019a(Wang et al, , 2020a, demonstrating its application potential for improving rice growth and combating root parasitic weeds. Very recently, Wang et al (2021) also demonstrated that increased sugar uptake and metabolism is likely the major reason for growth-promoting activities of zaxinone in rice and that zaxinone effect on root cell division activity in root meristem and on the number of cortex cell layers is likely caused by modulating cytokinin content.…”
Section: The Significance and Function Of Apocarotenoidsmentioning
confidence: 97%
“…The presence of zaxinone in Arabidopsis and its effect on hormone homeostasis shows the occurrence of ZAS‐independent routes for zaxinone synthesis and indicates a general growth regulatory activity in AM and non‐AM plant species. Interestingly, phenyl‐based compounds mimicking zaxinone activity were recently synthesized (Wang et al ., 2020a). Mimics of zaxinone (MiZax) MiZax3 and MiZax5 showed zaxinone activity.…”
Section: Cyclic and Acyclic Apocarotenoids With Signaling Propertiesmentioning
confidence: 99%
“…Mimics of zaxinone (MiZax) MiZax3 and MiZax5 showed zaxinone activity. These compounds rescued the root growth phenotype of a (zaxinone‐deficient) rice mutant, by promoting growth, and reduced SL accumulation in roots and root exudates of wild‐type plants (Wang et al ., 2020a). MiZax might be a valuable tool to study zaxinone function and its involvement in rice development and growth‐related processes further.…”
Section: Cyclic and Acyclic Apocarotenoids With Signaling Propertiesmentioning
confidence: 99%
“…Recently, we showed that the apocarotenoid zaxinone (C 18 , 3-OH-b-apo-13-carotenone) is a growth regulator and that other apo-13-carotenoids have a similar biological activity in determining strigolactone content (Wang et al, 2020a). In this work, we set out to identify apocarotenoids that may be involved in regulating seed germination in Arabidopsis.…”
Section: Introductionmentioning
confidence: 99%